Analisis Kombinasi itemset pada Bisnis Online dengan Teknik Asosiasi Data mining - Siregar, Muhammad Noor Hasan (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Online business is one of the industries that thrives on social media. With business competition starting to grow a lot these days, businesses are setting up online businesses to boost sales. One suggestion is to reduce the price on combination of items that are commonly purchased at the same time. Using the transaction data obtained through purchase, an association rule may be used to discover the rules for combinations of items. The association process uses an a priori algorithm to access sales transaction data. The positive results of this study can be used to produce the strategies in the development of online businesses.